2020
DOI: 10.3390/v12030346
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase TRIM21 Promotes HBV DNA Polymerase Degradation

Abstract: The tripartite motif (TRIM) protein family is an E3 ubiquitin ligase family. Recent reports have indicated that some TRIM proteins have antiviral functions, especially against retroviruses. However, most studies mainly focus on the relationship between TRIM21 and interferon or other antiviral effectors. The effect of TRIM21 on virus-encoded proteins remains unclear. In this study, we screened candidate interacting proteins of HBV DNA polymerase (Pol) by FLAG affinity purification and mass spectrometry assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 66 publications
0
40
0
Order By: Relevance
“…TRIM21 promotes the destruction of viral capsids via the proteasome and exposes the viral DNA or RNA to cytosolic nucleic acid sensors like cGAS and RIG-I [47]. In addition to NP, the polymerase complexes of viruses are subject to this means of disposal as TRIM32 targets the influenza polymerase subunit PB1 of several IAV strains to the proteasome via ubiquitination, while TRIM21 interacts with the hepatitis B virus (HBD) DNA polymerase to achieve the same effect for ubiquitination and proteasomal degradation [48,49].…”
Section: Antiviral Activity Of Trim Proteinsmentioning
confidence: 99%
“…TRIM21 promotes the destruction of viral capsids via the proteasome and exposes the viral DNA or RNA to cytosolic nucleic acid sensors like cGAS and RIG-I [47]. In addition to NP, the polymerase complexes of viruses are subject to this means of disposal as TRIM32 targets the influenza polymerase subunit PB1 of several IAV strains to the proteasome via ubiquitination, while TRIM21 interacts with the hepatitis B virus (HBD) DNA polymerase to achieve the same effect for ubiquitination and proteasomal degradation [48,49].…”
Section: Antiviral Activity Of Trim Proteinsmentioning
confidence: 99%
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, including rheumatoid arthritis, Systemic lupus erythematosus, and Sjogren’s syndrome ( Schulte-Pelkum et al, 2009 ). TRIM21 acts as an important factor involved in the innate immune responses against microbial infection, including bacterial, viral, and parasite ( Hos et al, 2020 ; Mu et al, 2020 ; Xie et al, 2020 ), however, little about TRIM21 is known for parasites infection. In this study, we reported that T. gondii RH and CEP infection upregulated the expression of TRIM21, thus restricted parasite replication through NF-ÎșB activation.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM25 targets CpG-rich sites in the genomes of Sindbis virus (SINV) and HIV-1, and inhibits translation of the incoming virus genome ( 61 , 62 ). TRIM21 suppresses hepatitis B virus (HBV) DNA replication by promoting the ubiquitination of HBV DNA polymerase ( 63 ). TRIM41 targets the viral nucleoprotein of vesicular stomatitis virus (VSV) for ubiquitination and subsequent protein degradation ( 64 ).…”
Section: Discussionmentioning
confidence: 99%